Penyuluhan Bahaya Petasan di Pesekutuan Anak dan Remaja (PAR) Rayon Remu Selatan Jemaat GKI Maranatha Remu Kota Sorong - Febry Talakua; Baktianita R. Etnis; Pricilya P. Ruhukail (Idea Pengabdian Masyarakat, 2021)
Playing firecrackers has become a tradition for the community, including children when welcoming big holidays such as Christmas, Eid, and New Year's Day. However, not infrequently playing firecrackers brings disaster to those who play them, especially children. Counseling about the dangers of firecrackers is one of the efforts to increase the understanding of children and adolescents about the dangers of firecrackers and their negative impacts. This activity aims to increase the knowledge of children and youth of the South Remu district of the GKI Maranatha Remu Congregation about the dangers of firecrackers. The method used is counseling with lecture and discussion methods. Submission of material through using PowerPoint. The results showed that the average pretest value of knowledge of the dangers of firecrackers in children and adolescents was 4.6 and the posttest was 8.4, with a change in value before and after counseling was given as much as 3.8 points. This activity concludes that the knowledge of children and adolescents about the dangers of firecrackers increases after being given counseling, for that it is hoped that the government, religious institutions, universities, and NGOs will always carry out outreach activities on the dangers of firecrackers to children and adolescents. Keywords: Knowledge, Danger of Firecrackers, Children, and Adolescents.